Biology of Thaumastocoris peregrinus in different eucalyptus species and hybrids - Soliman, Everton Pires [UNESP]; Wilcken, Carlos Frederico [UNESP]; Pereira, Jaqueline M. [UNESP]; Dias, Thaise K. R. [UNESP]; Zache, Bruno [UNESP]; Dal Pogetto, Mario H. F. A. [UNESP]; Barbosa, Leonardo R. (Springer, 2012)
The bronze bug Thaumastocoris peregrinus Carpintero & Dellap, (Hemiptera: Thaumastocoridae), originating in Australia, has been rapidly spreading in eucalyptus plantations in the Southern Hemisphere, including South Africa, Zimbabwe, Argentina, Uruguay, Paraguay and Chile. In Brazil, it was detected in 2008 in the states of São Paulo and Rio Grande do Sul. Due to incomplete knowledge about the biology of this pest, the present study evaluated the bioecology of T. peregrinus in different eucalyptus species and hybrids. The genetic materials utilized were: Eucalyptus camaldulensis, E. urophylla, E. grandis, '1277' (Hybrid E. grandis x camaldulensis-HGC), 'VM-1' (Hybrid E. urophylla x camaldulensis-HUC) and 'H-13' (Hybrid E. urophylla x grandis-HUG). The experiment was conducted in a climate-controlled chamber at a temperature of 26 +/- 1A degrees C, r.h. = 70% A +/- 10% and 12 h photophase. The biology of different genotypes indicated that the species E. urophylla and E. grandis are the most suitable for the development and reproduction of T. peregrinus, although all treatments enabled the bronze bug to develop and produce descendants. T. peregrinus developed and reproduced in the principal vegetal materials planted in the southern, central-west and northeastern regions of Brazil, constituting a potentially damaging insect pest to eucalyptus plantations.
Keywords: Bronze bug; Development; Exotic pests